2018
DOI: 10.1158/0008-5472.can-17-1435
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Neuropilin 1 from Microglia or Bone Marrow–Derived Macrophages Slows Glioma Progression

Abstract: Glioma-associated microglia and macrophages (GAM), which infiltrate high-grade gilomas, constitute a major cellular component of these lesions. GAM behavior is influenced by tumor-derived cytokines that suppress initial antitumorigenic properties, causing them to support tumor growth and to convert and suppress adaptive immune responses to the tumor. Mice that lack the transmembrane receptor neuropilin-1 (Nrp1), which modulates GAM immune polarization, exhibit a decrease in glioma volumes and neoangiogenesis a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 39 publications
2
44
1
Order By: Relevance
“…Our present comprehensive analysis of NRP1 expression in human GB, in combination with the conclusions from our murine glioma model [ 20 , 21 , 23 ], suggest that NRP1 is a valid target to pursue in future work. The observed correlation with genes characteristic of pro-tumorigenic GAMs, and the high cellular fractions found in the TME also suggest that there is a strong connection between NRP1 and tumor supporting cell populations.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Our present comprehensive analysis of NRP1 expression in human GB, in combination with the conclusions from our murine glioma model [ 20 , 21 , 23 ], suggest that NRP1 is a valid target to pursue in future work. The observed correlation with genes characteristic of pro-tumorigenic GAMs, and the high cellular fractions found in the TME also suggest that there is a strong connection between NRP1 and tumor supporting cell populations.…”
Section: Discussionmentioning
confidence: 90%
“…Based on our animal data [ 20 , 21 , 23 ], we sought to make meaningful extrapolations about NRP1 expression in human glioma. TCGA database enabled the mining of publicly available data before embarking on large scale human projects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent extensive reviews, including therapeutic approaches targeting microglia, are explained by Roesch et al 165 and Hambardzumyan et al 166 Recent work has sought to dissect further the pathological molecular mechanisms behind VEGF receptor-TGFβ receptor complex activities, 167 and indeed it has been shown that neuropilin 1 is a critical coreceptor in the induction of GAMs in a mouse model of glioma. 168 Furthermore, GAMs are thought to contribute to the poor efficacy of some oncolytic viruses by sequestering and inhibiting the replication of the therapeutic virus. 169 Specific to MMPs, the hypoxic environment characteristic of high-grade gliomas is known to induce MMP expression, and macrophages can independently induce MMP9 expression from glioma cells, with a slight additive effect in a hypoxic setting.…”
Section: Glioma-associated Microglia/macrophagesmentioning
confidence: 99%